Limited DNA methylation variation and the transcription of MET1 and DDM1 in the genus Chrysanthemum (Asteraceae): following the track of polyploidy - Wang, Haibin; Qi, Xiangyu; Chen, Sumei; Fang, Weimin; Guan, Zhiyong; Teng, Nianjun; Liao, Yuan; Jiang, Jiafu; Chen, Fadi (Frontiers in Plant Science, 2015)
Polyploidy has been recognized as a widespread and common phenomenon among flowering plants. DNA-5'-CCGG site cytosine methylation is one of the major and immediate epigenetic responses of the plant genome. Elucidating the ways in which altered C-methylation patterns, either at the whole genomic level or at specific sites can affect genome stability in polyploidy will require substantial additional investigation. Methylation-sensitive amplification polymorphism (MSAP) profiling was used to evaluate variation in C-methylation among a set of 20 Chrysanthemum species and their close relatives of varying ploidy levels from diploid to decaploid. The range in relative C-methylation level was within 10%, and there was no significant difference neither between different ploidy levels nor between different species in the same ploidy level. The transcript abundances of MET1 and DDM1 genes, which both involved in the regulation of C-methylation at CpG sites, were enhanced with increased ploidy level, but only MET1 was positively correlated with the nuclear DNA content. Considering the key role of MET1 in maintaining CpG methylation, the limited variation observed with respect to C-methylation may reflect a balance between the increased activity of MET1 in the higher ploidy genomes and the larger number of CpG dinucleotide sites available for methylation.